Thermal studies on nickel(II) 4-iodopyrazole complexes - Takahashi, P. M.; Frem, Regina C. G.; Netto, A. V. G.; Mauro, A. E.; Matos, J. R. (Springer, 2007)
This work describes the synthesis, IR and UV-Vis spectroscopic characterization as well the thermal behavior of the [NiCl2(HIPz)(4)]center dot C3H6O (1), [Ni(H2O)(2)(HIPz)(4)](NO3)(2) (2), [Ni(NCS)(2)(HIPz)(4)] (3) and [Ni(N-3)(2)(HIPz)(4)] (4) (HIPz = 4-iodopyrazole) pyrazolyl complexes. TG experiments reveal that the compounds 1-4 undergo thermal decomposition in three or four mass loss steps yielding NiO as final residue, which was identified by X-ray powder diffraction.
Keywords: DSC; 4-iodopyrazole; nickel(II); pseudohalides; TG